Funcionamiento familiar y riesgo de embarazo en adolescentes - Garcia Rebaza, Julia Yuliana (2020)
The present research study of quantitative, descriptive, correlational and cross sectional type was carried out in Virgen Del Carmen Educational Institution, El Porvenir District with the objective of determining the relationship between the level of family functioning and the risk of pregnancy in teenagers. The sample consisted of 92 teenage women. Two evaluation scales designed according to the research objectives were used as a data collection instrument. The analysis of the relationship between the variables was carried out using the correlational statistical test Tau B of Kendall. The results found were: of the 47 adolescents who presented a medium risk of pregnancy, 78 percent had medium family functioning, 11 percent had high family and another 11 percent had a low family functioning. Likewise, of the 30 adolescents who presented a high risk of pregnancy, 87 percent had a low family functioning and of the 13 percent had a medium family functioning and15 adolescents who presented a low risk of pregnancy, 80 percent had a high family functioning and 20 percent had medium family functioning. Therefore, it was concluded that there is a statistically significant relationship (p = 0.000) between family functioning and the risk of adolescent pregnancy.